2017
DOI: 10.1080/21690707.2017.1327757
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes and wonders of intrinsic disorder: Stability of instability

Abstract: This article continues a series of short comments on the paradoxes and wonders of the protein intrinsic disorder phenomenon by introducing the "stability of instability" paradox. Intrinsically disordered proteins (IDPs) are characterized by the lack of stable 3D-structure, and, as a result, have an exceptional ability to sustain exposure to extremely harsh environmental conditions (an illustration of the "you cannot break what is already broken" principle). Extended IDPs are known to possess extreme thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 208 publications
1
30
0
Order By: Relevance
“…Disordered protein domains exhibit an increased surface area for interaction, which can be beneficial for interaction with multiple binding partners. Self-assembling IDPs (intrinsically disordered proteins) can form higher-ordered protein complexes, where disordered protomers undergo binding-induced folding during super-complex formation 33,34,35 , which also appears to be the case when IM30 rings form in solution. Vice versa, IM30 rings appear to disassemble upon membrane binding and condensate into extended carpets on the membrane, which again requires interactions between the disordered C-termini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disordered protein domains exhibit an increased surface area for interaction, which can be beneficial for interaction with multiple binding partners. Self-assembling IDPs (intrinsically disordered proteins) can form higher-ordered protein complexes, where disordered protomers undergo binding-induced folding during super-complex formation 33,34,35 , which also appears to be the case when IM30 rings form in solution. Vice versa, IM30 rings appear to disassemble upon membrane binding and condensate into extended carpets on the membrane, which again requires interactions between the disordered C-termini.…”
Section: Discussionmentioning
confidence: 99%
“…These assemblies, which likely correspond to the IM30 carpet structures observed in the present study, have been identified in vivo to dynamically localize, preferably at stressed TM regions 3 . In fact, dynamic self-assembly is typically observed with IDPs, often involving liquidliquid phase separation 33,41,42 . In contrast to the formation of membrane-less organelles in cells, induced by liquid-liquid phase separation of IDPs, demixing into a condensed and a protein-light fraction (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of intrinsically disordered proteins (IDPs), 47 i.e., functional proteins lacking a well-defined tertiary structure, has challenged the traditional 48 sequence-structure-function paradigm [7,8]. IDPs constitute, in eukaryotes, a substantial part of the 49 cellular proteome and are involved in many biological processes that complement the functional 50 repertoires of ordered proteins [9,10]. Ever-increasing experimental evidence has revealed the IDPs, allowing them to interact with a broad range of substrates with relatively high-specificity and 90 low-affinity, often undergoing a disorder-to-order transition upon binding [2,8,26,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Disordered protein domains exhibit an increased surface area for interaction, which can be beneficial for interaction with multiple binding partners. Self-assembling IDPs (intrinsically disordered proteins) can form higher-ordered protein complexes, where disordered protomers undergo binding-induced folding during super-complex formation [33][34][35] , which also appears to be the case when IM30 rings form in solution. Vice versa, IM30 rings appear to disassemble upon membrane binding and condensate into extended carpets on the membrane, which again requires interactions between the disordered C-termini.…”
Section: Discussionmentioning
confidence: 99%
“…These assemblies, which likely correspond to the IM30 carpet structures observed in the present study, have been identified in vivo to dynamically localize, preferably at stressed TM regions 3 . In fact, dynamic self-assembly is typically observed with IDPs, often involving liquid-liquid phase separation 33,41,42 . In contrast to the formation of membrane-less organelles in cells, induced by liquid-liquid phase separation of IDPs, demixing into a condensed and a protein-light fraction (i.e., carpets and unassociated but membrane-attached protomers) appears to take place on the membrane surface in case of IM30.…”
Section: Discussionmentioning
confidence: 99%